Tissue Factor-Enriched Neutrophil Extracellular Traps Promote Immunothrombosis and Disease Progression in Sepsis-Induced Lung Injury - Zhang, Hao; Zhou, Yilu; Qu, Mengdi; Yu, Ying; Chen, Zhaoyuan; Zhu, Shuainan; Guo, Kefang; Chen, Wankun; Miao, Changhong (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Patients with sepsis may progress to acute respiratory dysfunction syndrome (ARDS). Evidences of neutrophil extracellular traps (NETs) in sepsis-induced lung injury has been reported. While the role of circulating NETs in the progression and thrombotic tendency of sepsis-induced lung injury remains elusive. The aim of this study is to investigate the role of tissue factor-enriched NETs in the progression and immunothrombosis of sepsis-induced lung injury. Methods: Human blood samples and an animal model of sepsis-induced lung injury were used to detect and evaluate NETs formation in the progress of ARDS patients. Immunofluorescence imaging, ELISA, western blotting and qPCR were performed to evaluate the in vitro NETs formation and their TF delivery ability. DNase, anti-TF antibody as well as thrombin inhibitors were applied to evaluate the contribution of thrombin to TF-enriched NETs formation and contribution of TF-enriched NETs to immunothrombosis of ARDS patients. Results: Significantly increased TF-enriched NETs were observed in ARDS patients and mice. Blockade of NETs in ARDS mice alleviated the disease progression indicated reduced lung wet/dry ratio and PaO2 level. In vitro data demonstrated thrombin-activated platelets were responsible for increased NETs formation and related TF exposure and subsequent immunothrombosis in ARDS patients. Conclusion: The interaction of thrombin-activated platelets with PMNs in the ARDS patients results in local NETs formation and delivery of active TF. The notion that NETs represent a mechanism by which PMNs release thrombogenic signals during a therothrombosis may offer novel therapeutic targets.